Reduction Of Agglomerated Manganese Ores In A 150 Kw Pilot Scale Furnace - Merete Tangstad; Thomas Brynjulfsen; Eli Ringdalen (The Minerals, Metals and Materials Society, 2014)
Manganese ore fines cannot be added to the submerged arc furnace directly as they will prevent even gas flow through the burden. Low gas permeability in the burden will lower the degree of pre-reduction of ore subsequently increase the carbon and energy consumption of the process. In order to utilize manganese ore fines in the furnace, they are typically agglomerated into sinter. In this work, the melting and reduction properties of Gabonese sinter and Gabonese ore have been investigated in pilot scale experiments. Two experiments were conducted, one with 100% sinter as manganese source and one with 50/50 sinter and ore. Lime was used to achieve a charge basicity of 0.72 in both experiments. The composition of slag samples from the excavation of the furnace was established using EPMA(WDS), and the composition of the tapped slag and metal was found using XRF. It was found that while the coke-bed size would determine the tapped slag composition, the melting behavior of the Mn source would determine the mixing with lime.